For a political ecology of knowledges. How can we inherit STS (Science, Technology and Society)? - Lalande, Antoine; Le Marec, Joëlle (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This article’s stake is the protection of relationships and experiences of knowledges that can be felt as alive. This is why it also deals with the deadly processes that reach institutions of research that the category of « zombie » tries to describe when applied to technologies or concepts. After having showed how our project try to reconnect with the idea of a political ecology of knowledges, we explain why this issue inherits the epistemological and political debates that characterized the raising of French STS in the 1970’s. Then, by going back on our respective researches, we demonstrate how the living o zombifying dimension of knowledges is something that can be felt above all from the fieldwork, and more especially from meeting’s situations with the public of these knowledges. In this way, we stand for the idea that inquiry may constitute a collective initiative from which putting into practice a political ecology of knowledges is possible. This ecology would therefore consist in probing the dimension alive or dead of sciences in society, more specially in the interstices of the places of production of professional sciences and its peripherals.
Keywords: Knowledge; ecology; STS; heritage; fieldwork